Fish biodiversity and livelihood status of fishermen living around the Titas river of Bangladesh. - Afrad, MSI; Yeasmin, S; Haque, ME; Sultana, N; Barau, AA; Rana, S (Journal of Bio-Science, 2019)
Fisheries biodiversity is important especially for the rural poor who often rely on fishing to earn their livelihoods. This study was carried out to examine the fish species diversity and livelihood status of fishermen around the Titas River falls under the villages of Radhanagar and Uzanchar at Bancharampur upazila of Brahmanbaria district. Data were collected from randomly selected 80 fishermen and analyzed using descriptive statistical tools, viz. frequency and percentage. A total of 55 fisheries species under 10 orders and 20 families were recorded from the Titas River. Cypriniformes was the most dominant order comprising 19 species followed by Siluriformes (12 species), Perciformes (8 species), Synbranchiformes (4 species), Channidiformes (3 species), Beloniformes (1 species), Osteoglossiformes (2 species), Clupeiformes (2 species) and Tetraodontiformes (2 species). Results also revealed that 60.0% of fishermen were belonged to the age group 31–50 years and 75.0% of them had no individual water body of their own. All of the fishermen were male, of whom 83.7% were married living in kutcha house (55.0%) and 52.5% of their families were nuclear type consisting of husband wife and their children. The illiteracy rate among fishermen was 26.0%, while 41.3% of them could sign only. Many fishermen (68.8%) were able to sell their catch at local market and 60.0% had an annual income ranging BDT 71,000–100,000 (= USD 844.887–1189.92). Overall, fish biodiversity in the Titas River is declining as compared to abundance observed from previous findings. Moreover, the fishermen of that place are leading a poor life having lower income than that of the government minimum wage, a basic pay of BDT 8,250 per month. J. bio-sci. 27: 59-67, 2019